Memoria Escrita De La Obra “Estados De Estado” Acercamientos A Un Trabajo De Creación Y Puesta En Escena (2017)
This degree work constitutes the culmination of the Research process training of the master artist in training for the Bachelor's Degree in Artistic Education with emphasis in Dance and Theater - Faculty of Education of the Antonio University Narino. Their developments, contributions, scope, questions and projections contribute to the growth of the Performing Arts Didactic Research Group and is enrolled in the Line that bears the same name. In particular, it is part of the studies of the Artistic Written Memory subline, as part of this, Written Memory of the work “States of State” Approaches to a work of creation and staging.